Petisi Online dan Keterampilan Partisipatoris Warga Negara - Nazwarini Khairunisa; Ronni Juwandi; Dinar Sugiana Fitrayadi (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study aimed to examine the efficacy of online petitions in enhancing citizen participation skills. Employing a quantitative approach with descriptive methods, the research focused on the population of active students enrolled in the Teaching and Education Faculty at Sultan Ageng Tirtayasa University. Simple random sampling was utilized as the sampling technique. The validity and reliability of the data were assessed using the SPSS application version 26, while effectiveness was measured through the Likert Summarizing Rating (LSR) method. The findings indicated a significant level of effectiveness in developing citizen participatory skills through online petitions, as evidenced by the assessment score of 20.139 > Q2. The average ideal score demonstrated an overall research effectiveness percentage of 73%. These outcomes highlight the potential of online petitions to foster citizen engagement, as they encourage individuals to exhibit intellectually supported and active participation as citizens. Online petitions serve as a facilitator for citizens to raise and address pertinent issues, thereby aiding in the cultivation of civic skills. This research contributes to the understanding of the role and impact of online petitions in nurturing citizen participatory skills, emphasizing the importance of online platforms in promoting active citizenship and fostering democratic engagement.